Analisis Penyebab Penurunan Kualitas Produksi Padi (Varietas Ramos) Dengan Metode Fishbone Analisis Di Desa Sitoluama Kecamatan Laguboti Kabupaten Toba - Pangaribuan, Raveena Lestari; Hermanto, Bambang (Universitas Medan Area, 2023)
This research was to analyze and identify the problem of decreasing quality of rice production (Ramos Variety) in Sitoluama Village, Laguboti District, Toba Regency. Fishbone analysis is used to categorize various potential causes of a problem or subject matter in an easy to understand and neat way. The results showed that the problem faced by rice farmers in Sitoluama Village, Laguboti District was a decrease in the quality of rice production (Ramos Variety). The causal factors that affect the quality of rice production in Sitoluama Village, Laguboti District, Toba Regency, namely: Farmer Factors, Cultivation Technique Factors, Material Factors, Machinery Factors/Agricultural Equipment, Environmental Factors, Management Factors. The most appropriate solution to the problems experienced by rice farmers in Sitoluama Village, Laguboti District, Toba Regency in improving the quality of rice includes, Man Factor: Collaborating with the village government to bring in extension workers and conducting education training programs, Machine factor: Encouraging farmers to form agricultural cooperatives to collectively purchase agricultural equipment, Mother Nature factor: Farmers can consider proper planting scheduling to avoid the most intense rainy season, Management: Developing and implementing an integrated agricultural information system can help improve planning and monitoring efficiency